A rare case of constrictive pericarditis as initial manifestation of paediatric anaplastic large cell lymphoma requiring urgent pericardiectomy. (2020) - Iqbal, Sara; Sohail, Abdul Ahad; Asif, Narmeen; Khan, Muhammad Rahil; Siddique, Sabeehuddin; Fatimi, Saulat Hasnain
Highlights: 11 year old child who presented with effusive Constrictive Pericarditis. Required urgent Pericardiectomy for managing right heart failure. Histopathology showed Anaplastic Large Cell Lymphoma. Abstract: Constrictive pericarditis (CP) is a rare end stage inflammatory disorder affecting both parietal and visceral pericardium leading to a right heart failure. Malignancy is the least common cause of CP. Anaplastic large cell lymphoma (ALCL) accounts for 10–15% of all Non-Hodgkin lymphomas in children. Very few case reports have reported ALCL that is involving the heart and only two have been published involving pericardium but all were managed medically. We present an interesting case of an 11 year old child who presented with an effusive CP that required urgent Pericardiectomy for managing right heart failure. His histopathology was positive for ALK + ALCL.